2019
DOI: 10.1038/s41598-019-40903-0
|View full text |Cite
|
Sign up to set email alerts
|

Crotoxin promotes macrophage reprogramming towards an antiangiogenic phenotype

Abstract: Crotoxin (CTX) is the primary toxin of South American rattlesnake Crotalus durissus terrificus venom. CTX reduces tumour mass, and tumour cell proliferation and these effects seem to involve the formation of new vessels. Angiogenesis has a key role in tumour growth and progression and is regulated by macrophage secretory activity. Herein, the effect of CTX on macrophage secretory activity associated with angiogenesis was investigated in vitro. Thymic endothelial cells (EC) were incubated in the presence of mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 68 publications
0
12
0
5
Order By: Relevance
“…Purification and phospholipase activity of the CTX was performed as described in previous studies ( Fraenkel-Conrat and Singer, 1956 ; Laemmli, 1970 ; Lobo de Araujo and Radvanyi, 1987 ; Faure and Bon, 1988 ; Sampaio et al, 2003 ; Sampaio et al, 2006a ; Sampaio et al, 2006b ; Brigatte et al, 2016 ; de Araujo Pimenta et al, 2019 ). Briefly, crude venom solution (CdtV) was subjected to anion-exchange chromatography, using a Mono-Q HR 5/5 column in an FPLC system (Pharmacia, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Purification and phospholipase activity of the CTX was performed as described in previous studies ( Fraenkel-Conrat and Singer, 1956 ; Laemmli, 1970 ; Lobo de Araujo and Radvanyi, 1987 ; Faure and Bon, 1988 ; Sampaio et al, 2003 ; Sampaio et al, 2006a ; Sampaio et al, 2006b ; Brigatte et al, 2016 ; de Araujo Pimenta et al, 2019 ). Briefly, crude venom solution (CdtV) was subjected to anion-exchange chromatography, using a Mono-Q HR 5/5 column in an FPLC system (Pharmacia, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…For counting the migrating cells in the field induced by the probe, the images were inserted into the rules on the left and right edges of the field, based on the image obtained in the T0 coverslip. After insertion of dashed lines, the count of migrating cells in the field was performed ( de Araujo Pimenta et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…C. durissus terrificus causes significant mortality across South America, yet components of its venom have been extensively researched for potential therapeutic applications [9][10][11][12]. In vitro studies have shown that the venom's principal neurotoxin, crotoxin (CTX), and its isolated basic phospholipase A 2 (PLA 2 ) subunit, downmodulate the expression of surface molecules with crucial stimulatory function on immune cells.…”
Section: Introductionmentioning
confidence: 99%